A Delaminated Defect‐Rich ZrO2 Hierarchical Nanowire Photocathode for Efficient Photoelectrochemical Hydrogen Evolution. Issue 4 (22nd September 2017) - Rahman, Md Anisur; Thomas, Joseph P.; Leung, Kam Tong
Abstract: An efficient way to combat the energy crisis and the greenhouse gas effect of fossil fuels is the production of hydrogen fuel from solar‐driven water splitting reaction. Here, this study presents a p‐type ZrO2 nanoplate‐decorated ZrO2 nanowire photocathode with a high photoconversion efficiency that makes it potentially viable for commercial solar H2 production. The composition of oxygen vacancy defects, low charge carrier transport property, and high specific surface area of these as‐grown hierarchical nanowires are further improved by an hydrofluoric acid (HF) treatment, which causes partial delamination and produces a thin amorphous ZrO2 layer on the surface of the as‐grown nanostructured film. The presence of different types of oxygen vacancies (neutral, singly charged, and doubly charged defects) and their compositional correlation to the Zr x + oxidation states (4 > x > 2) are found to affect the charge transfer process, the p‐type conductivity, and the photocatalytic activity of the ZrO2 nanostructured film. The resulting photocathode provides the highest overall photocurrent (−42.3 mA cm −2 at 0 V vs reversible hydrogen electrode (RHE)) among all the photocathodes reported to date, and an outstanding 3.1% half‐cell solar‐to‐hydrogen conversion efficiency with a Faradaic efficiency of 97.8%. Even more remarkable is that the majority of the photocurrent (69%) is produced in the visible light region. Abstract : Defect‐rich, partially delaminated, p‐type hierarchical ZrO2 nanowires show extraordinary photoelectrochemical water splitting property in the visible light with a record photocurrent density of −42.5 mA cm −2 at 0 V versus RHE and a high half‐cell solar‐to‐hydrogen conversion efficiency above 3.1%.